Energy Conflicts and Differential Profits: An Update - Shimshon Bichler; Jonathan Nitzan (The Bichler and Nitzan Archives, 2014)
During the late 1980s and early 1990s, we identified a new phenomenon that we called `energy conflicts' and showed that these conflicts were intimately linked to the differential profitability of the leading oil companies. This link remains as true today as it was in the early 1970s. Like earlier energy conflicts, the `Arab Spring', the outsourced wars that followed and the third Gulf War against ISIS continue to march to the drum beat of differential profits.
Keywords: 330; crisis; differential accumulation; energy conflicts; Middle East; Petro-Core